Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
c) Ta có: \(\dfrac{3}{5}+\dfrac{-5}{20}+\dfrac{30}{75}+\dfrac{-7}{4}\)
\(=\dfrac{3}{5}+\dfrac{2}{5}+\dfrac{-1}{4}+\dfrac{-7}{4}\)
\(=1-2=-1\)
Giải:
a)-1/12+4/3=-1/12+16/12=15/12=5/4
b)(-4/14-3/15)-(1/5-20/35-(-1)).7
=-17/35-22/35.7
=-17/35-22/5
=-171/35
c)3/5+-5/20+30/75+-7/4
=3/5+-1/4+2/5+-7/4
=(3/5+2/5)+(-1/4+-7/4)
=1+-2
=-1
d)5/6.-12/14+7/13
=-5/7+7/13
=-16/91
e)2/-9-5/-36-1/4
=-1/12-1/4
=-1/3
f)2/23+-5/12+7/18+21/23+-7/12
=(2/23+21/23)+(-5/12+-7/12)+7/18
=1+-1+7/18
=7/18
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\)
\(\frac{4}{9}.x=\frac{1}{9}\)
\(\Rightarrow x=\frac{1}{9}:\frac{4}{9}\)
\(\Rightarrow x=\frac{1}{9}.\frac{9}{4}\)
\(\Rightarrow x=\frac{1}{4}\)
Vậy \(x=\frac{1}{4}\)
\(b.\)
\(\frac{7}{18}.x-\frac{2}{3}=\frac{5}{18}\)
\(\Rightarrow\frac{7}{18}.x=\frac{5}{18}+\frac{2}{3}\)
\(\Rightarrow\frac{7}{18}.x=\frac{5}{18}+\frac{12}{18}\)
\(\Rightarrow\frac{7}{18}.x=\frac{17}{18}\)
\(\Rightarrow x=\frac{17}{18}:\frac{7}{18}\)
\(\Rightarrow x=\frac{17}{18}.\frac{18}{7}\)
\(\Rightarrow x=\frac{17}{7}\)
Vậy \(x=\frac{17}{7}\)
\(c.\)
\(x:-\frac{1}{12}=\frac{7}{12}\)
\(\Rightarrow x=\frac{7}{12}.-\frac{1}{12}\)
\(\Rightarrow x=-\frac{7}{144}\)
Vậy \(x=-\frac{7}{144}\)
\(d.\)
\(\frac{4}{9}-\frac{7}{8}.x=-\frac{2}{3}\)
\(\Rightarrow\frac{7}{8}.x=\frac{4}{9}-\left(-\frac{2}{3}\right)\)
\(\Rightarrow\frac{7}{8}.x=\frac{4}{9}+\frac{2}{3}\)
\(\Rightarrow\frac{7}{8}.x=\frac{4}{9}+\frac{6}{9}\)
\(\Rightarrow\frac{7}{8}.x=\frac{10}{9}\)
\(\Rightarrow x=\frac{10}{9}:\frac{7}{8}\)
\(\Rightarrow x=\frac{10}{9}.\frac{8}{7}\)
\(\Rightarrow x=\frac{80}{63}\)
Vây \(x=\frac{80}{63}\)
\(e.\)
\(-\frac{5}{14}:x=-\frac{3}{10}\)
\(\Rightarrow x=-\frac{5}{14}:-\frac{3}{10}\)
\(\Rightarrow x=-\frac{5}{14}.-\frac{10}{3}\)
\(\Rightarrow x=\frac{5}{7}.\frac{5}{3}\)
\(\Rightarrow x=\frac{25}{21}\)
Vậy \(x=\frac{25}{21}\)
\(g.\)
\(\frac{1}{6}+\frac{-5}{7}:x=-\frac{7}{18}\)
\(\Rightarrow-\frac{5}{7}:x=-\frac{7}{18}-\frac{1}{6}\)
\(\Rightarrow-\frac{5}{7}:x=-\frac{7}{18}-\frac{3}{18}\)
\(\Rightarrow-\frac{5}{7}:x=-\frac{10}{18}\)
\(\Rightarrow-\frac{5}{7}:x=-\frac{5}{9}\)
\(\Rightarrow x=-\frac{5}{7}:-\frac{5}{9}\)
\(\Rightarrow x=-\frac{5}{7}.-\frac{9}{5}\)
\(\Rightarrow x=\frac{9}{7}\)
Vậy \(x=\frac{9}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{2}{3}+\dfrac{19}{35}=\dfrac{70+57}{105}=\dfrac{127}{105}\)
b: \(=\dfrac{2}{7}+\dfrac{2}{5}=\dfrac{24}{35}\)
c: \(=\dfrac{7}{12}-\dfrac{14}{2}=\dfrac{7-84}{12}=\dfrac{-77}{12}\)
d: \(=\dfrac{-15}{60}-\dfrac{1}{8}=-\dfrac{3}{8}\)
e: \(=-\dfrac{12}{72}+\dfrac{1}{18}=\dfrac{-3}{18}+\dfrac{1}{18}=\dfrac{-2}{18}=\dfrac{-1}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a; - \(\dfrac{10}{13}\) + \(\dfrac{5}{17}\) - \(\dfrac{3}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{11}{20}\)
= - (\(\dfrac{10}{13}\) + \(\dfrac{3}{13}\)) + (\(\dfrac{5}{17}\) + \(\dfrac{12}{17}\)) - \(\dfrac{11}{20}\)
= - 1 + 1 - \(\dfrac{11}{20}\)
= 0 - \(\dfrac{11}{20}\)
= - \(\dfrac{11}{20}\)
b; \(\dfrac{3}{4}\) + \(\dfrac{-5}{6}\) - \(\dfrac{11}{-12}\)
= \(\dfrac{9}{12}\) - \(\dfrac{10}{12}\) + \(\dfrac{11}{12}\)
= \(\dfrac{10}{12}\)
= \(\dfrac{5}{6}\)
c; [13.\(\dfrac{4}{9}\) + 2.\(\dfrac{1}{9}\)] - 3.\(\dfrac{4}{9}\)
= [\(\dfrac{52}{9}\) + \(\dfrac{2}{9}\)] - \(\dfrac{4}{3}\)
= \(\dfrac{54}{9}\) - \(\dfrac{4}{3}\)
= \(\dfrac{14}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a; \(\dfrac{9}{4}\) - \(\dfrac{-11}{4}\)
= \(\dfrac{9}{4}\) + \(\dfrac{11}{4}\)
= \(\dfrac{20}{4}\)
= 5
b; \(\dfrac{7}{8}\) - \(\dfrac{3}{-8}\) - \(\dfrac{1}{8}\)
= \(\dfrac{7}{8}\) + \(\dfrac{3}{8}\) - \(\dfrac{1}{8}\)
= \(\dfrac{7+3-1}{8}\)
= \(\dfrac{9}{8}\)
c; \(\dfrac{-5}{21}\) - \(\dfrac{25}{21}\) - \(\dfrac{-1}{21}\)
= \(\dfrac{-5}{21}\) - \(\dfrac{25}{21}\) + \(\dfrac{1}{21}\)
= \(\dfrac{-5-25+1}{21}\)
= \(\dfrac{-29}{21}\)
a/\(\frac{1}{3}\) b/\(\frac{2}{3}\)
c/\(\frac{-3}{7}\) d/\(\frac{17}{18}\)